Kafala System and Precariat Exploitation at Qatar World Cup Title - Muhammad Fachrul (CV. Syntax Corporation Indonesia, 2024)
Football, as a sport that holds human spirit, passion, and pride, has transformed into a global phenomenon that includes political, cultural, and business aspects. This study is based on qualitative research methods. According to Bakry (2019), qualitative research is intended to expand understanding related to social phenomena, activities, and processes. The World Cup has the official name FIFA™ World Cup is an international football competition that is held once in four years and involves as many as 32 participating countries competing with each other for the title of world champion in the field of football (FIFA, 2023). The study concluded that the kafala work system in Qatar creates exploitative relations with migrant workers.